PENGARUH BERMAIN MEDIA PLASTISIN TERHADAP PERKEMBANGAN ANAK PRASEKOLAH - Daliana " Aryati; Ganis " Indriati; Siti Rahmalia Hairani Damanik (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Preschool are early childhood, which age in 3-6 years old. This situation when physical development and a great personality and their motoric development that occurs continuously. Development is the increaseased capability or function of every organ system of the body. The nature of using playdough is essentially to stimulate development. The purpose of this research was to looking for playdough influence on the development of preschool. The design of this research was quasy experimental design. The total sample are 34 respondents with purposive sampling technique. The instrument is used Denver Development Screening Test (DDST) with modification percent. The result showed that pretest of development of preschool in experimental group was 29,65. The result showed that pretest of development of preschool in control group was 25,35. The result showed that post test of development of preschool in experimental group was 33,18. The result showed that post test of development of preschool in control group was 25,36. The test results of Mann-Whitney value of development of preschool after the intervention in the experimental group and the untreated control group was obtained p value (0.015) < α (0.05). It can be concluded that there is a significant difference average value of preschool child development experimental and control groups after intervention by media playdough. Keyword: Development, playdough, preschool